La fiche à l'école maternelle : un objet littératié paradoxal - Ariane Richard-Bossez (Nantes Université, 2016)
This article is about the role played by worksheets in the building of knowledge in French preschool and the differentiations that these teaching aids can produce. It is built on a field study carried out in six classes of grande section (third and last year of preschool, intended for 5/6-year old children) from different social backgrounds. This article describes three dimensions related to the use of worksheets in preschool classes which, when they are combined, participate to differentiations in the construction of the pupil's knowledge. First, it shows that worksheets are not neutral mediums insofar as they are based on a specific learning mode and they contribute to shaping the knowledge itself. Then, it presents the different registers from which pupils interpret worksheets, by stressing that only a minority of pupils rely on a literacy mode which corresponds to school expectations. Finally, it underlines how the material dimension the worksheets tends to strengthen the least literacy approaches to knowledge. Thus, this article leads to a better understanding of how worksheets fail to allow pupils to integrate the literacy dimension if they do not master it previously, and how the relation to knowledge and the materiality of these teaching aids contribute, on the contrary, to reinforcing the registers which are most distant from school expectations.